2001
DOI: 10.1515/hf.2001.093
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a Soft Rot-Like Decay Pattern Caused by Coniophora puteana (Schum.) Karst. in Sapelli Wood (Entandrophragma cylindricum Sprague)

Abstract: Summary The decay patterns of brown and soft rot fungi in Sapelli wood (Entandrophragma cylindricum Sprague), with respect to natural durability, were examined by light and transmission electron microscopy as well as UV spectroscopy. Analyses revealed that the typical brown rot fungus Coniophora puteana can cause a soft rot-like decay in the sapwood of Sapelli at high moisture contents of approx. 100%. In accordance with the decay pattern of the typical soft rot fungus Chaetomium globosum, the hyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Delignification is limited to a very narrow region around the zone of hyphal growth as indicated clearly by low absorbances around these structures (Abs 280nm s0.09-0.22). The reason for this observation is clear: the lignolytic enzymes do not diffuse deeply into the secondary wall but rather act in close proximity to the hyphae, as also described by Kleist and Schmitt (2001) for brown rot fungi.…”
Section: Umspmentioning
confidence: 67%
See 1 more Smart Citation
“…Delignification is limited to a very narrow region around the zone of hyphal growth as indicated clearly by low absorbances around these structures (Abs 280nm s0.09-0.22). The reason for this observation is clear: the lignolytic enzymes do not diffuse deeply into the secondary wall but rather act in close proximity to the hyphae, as also described by Kleist and Schmitt (2001) for brown rot fungi.…”
Section: Umspmentioning
confidence: 67%
“…Soft rot is characterized by the formation of narrow erosion cavities and hyphal tunneling that implies the presence of enzymes with a very low diffusibility (Blanchette et al 1985). Kleist and Schmitt (2001) also found that the lignolytic activity was restricted to a very close vicinity of the areas of hyphal tunneling in the case if decay was caused by brown rot and soft rot in wood of Sapeli (Entandrophragma cylindricum Sprague).…”
Section: Introductionmentioning
confidence: 96%
“…The degradation of the cell walls and the increased cavity formation (Flournoy et al, 1991;Highley et al, 1983;Rawat et al, 1998), especially in the S 2 layer (Kleist and Schmitt, 2001;Larsen et al 1995;Lee et al, 2004), might have increased the number of capillaries as well as the surface area. In our material these kind of changes were visible in the scanning electron microscope (SEM) image (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Baum et al (2000) studied the effects of fungal infection (by Ustulina deusta) on the G-layer within beech tension wood fibres in the reaction zone and found that this made the tree infiltrate the G-layer with poly phenolics, presumably as a means of protection. Kleist and Schmitt (2001) characterised the decay pattern caused by Coniophora puteana in Sapelli wood (Entandrophragma cylindricum) and found no lignin degradation in the vicinity of the cell wall cavities caused by the fungi. Blanchette et al (1997) used UV microspectroscopy to show loss of lignin within the cell walls of loblolly pine wood chips (Pinus taeda) decayed by the white rot fungus Ceriporiopsis subvermispora.…”
Section: Cell Wall Degradationmentioning
confidence: 99%